Digitalizing Higher Education in Light of Sustainability and Rebound Effects—Surveys in Times of the COVID-19 Pandemic - Marlen Gabriele Arnold (MDPI AG, 2021)
The COVID-19 pandemic has focused attention not only on health and social issues, but on the issue of digital transformation as well. Within a very short time, universities had to convert their courses to digital formats and university life was reduced to a minimum. To shed light on how the COVID-19 pandemic has affected universities, we investigated the following questions: How was this transformation accomplished? What advantages and disadvantages did it bring with it? How sustainable was this transformation? and What can the future of higher education look like? This study is based on the responses to two questionnaires for university staff and students conducted at the Chemnitz University of Technology between mid-July and September, 2020 (n = 369), and between February and March, 2021 (n = 252). Both questionnaires were analysed using descriptive statistics and qualitative content analysis. The results show wide variations in response to digital teaching and learning. Digital teaching and working/learning from home have brought both multiple benefits and multiple challenges at the same time. Working and learning from home was perceived as both enriching and overwhelming—even for the same individual. Respondents appreciated the flexibility associated with digital teaching, even though digital teaching was perceived as imposing excessive demands. This study reveals striking gaps in our knowledge and our actions linking digital transformation and sustainability and highlights how digital teaching can be further developed.